Reactive Extraction For The Synthesis Of Fame/Faee From Jatropha Curcas L. Seeds - Shuit , Siew Hoong (2010)
Owing to the non-edible nature and suitability for cultivation in local tropical climate in Malaysia, Jatropha oil (Jatropha curcas) is believed to be a potential oil source for biodiesel production after palm oil. Biodiesel from Jatropha curcas L. seed is conventionally produced via two steps method; extraction of oil and subsequent esterification/transesterification to fatty acid methyl esters (FAME) or commonly known as biodiesel. Contrary, in this research work, a single step in-situ extraction, esterification and transesterification (or collectively known as reactive extraction) of Jatropha curcas L. seed to biodiesel was studied. The Jatropha seed used in this study was found to have a moisture and oil content of 5.39% and 54.4% respectively, while the extracted oil was found to have high free fatty acid (FFA) content. In the preliminary study, this research work began by studying the effect of different Jatropha seed size and moisture content on the reactive extraction process.